On Fracture Pattern of Polymer Canisters at Explosion of Various Media - I. S. Taubkin; A. V. Akhachinskii; A. R. Saklantii; Yu. A. Robot’ko; A. F. Kozhukhov; V. V. Gulenkov (Теория и практика судебной экспертизы, 2025)
The fracture pattern of polymer canisters found at an explosion site may contain information on the nature of an exploded medium – gas or an air-vapor mixture or a condensed explosive substance. Due to the fact there was no data in the available technical literature on the fracture pattern of polymer canisters’ explosions of various nature, experts conducted special studies under examination of one of the criminal cases the results of which are presented in this article.